TEACHERS’ EXPERIENCES ON THE USE OF GOOGLE CLASSROOM - Harjanto, Almio Susetyo; Sumarni, Sri (Universitas Muhammadiyah Semarang, 2019)
Technology has impacted in most of the sectors, including education field. Nowadays, many schools have incorporated technology through the utilization of Information and Communication Technologies (ICT) into the learning. The use of platforms such as Google Classroom is one of the ways to fit the best classroom practices. This study reveals the teacher’s perception on the use of Google Classroom as a learning media. The qualitative research design which applies interview method is carried out. Seven high school teachers in Tangerang Selatan, Indonesia, who have actively integrated Google Classroom in their teaching for at least 1 year became the participants. Findings showed that teachers use it as a facilitation tool for managing students’ tasks, organizing classroom and accommodating students’ interaction. In general, teachers perceived the use of Google Classroom was very helpful to conduct their virtual classroom. However, teachers stated that they needed to maximize other features of Google Classroom as they hadn’t explored all which would surely bring benefits for their professional development.